Max Weber e a racionalização: passos iniciais para a compreensão e a crítica do mundo moderno - Secches, Pedro (2014)
This dissertation s objective is to explore, within Max Weber s work, the concept of rationalization and its importance in the formation of the modern world. As proposed, the process of rationalization is presented as an historic process common to every civilization. A process that, regarding the western civilization, has a distinct peculiarity: the western formal rationality. Which, according to Weber, is the responsible for the formation of the modern world. However, the objective of this research is not limited to describing the formation of the modern world from the development of the western rationalized civilization, but also consists of discussing the possible effects of this process in modern society, according to the weberian critic. In order to do so, it is proposed, firstly, to analyze the author s thought regarding the historical period in which he lived, and also regarding the thinkers that served as influence and/or inspiration on the creation of his own critical analysis. Finally, the concept of rationalization is explored from three different, but complementary, approaches: 1) rationalization as an historic process, 2) the peculiar rationalization of the West in the formation of the modern world, and 3) Weber s critic of the rationalized modern world